2021
DOI: 10.22374/ijmsch.v4i1.48
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Health Promotion in Waiting Rooms: An Observational Study

Abstract: Issue addressedCurrently, in Australia, male health outcomes are poorer than that of females, with males experiencing a lower life expectancy, accounting for 62% of the premature deaths. Exploring male-specific health promotional material in health facility waiting rooms provides an opportunity to examine available health information. There are few studies on health-related education for patients, families and carers in general practitioner (GP) waiting rooms, and no studies on male-specific health material co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…If this is the case, strategies to increase awareness and improve health seeking behaviour in men may lead to more timely recognition and treatment of infection, thus reducing the risk of onset of organ failure, and therefore sepsis. A recent observational study of health promotional material in facility waiting rooms in NSW indicated only 3.1% of health promotional materials were male specific, compared to 15.3% female specific health promotion materials, 25 presenting one potential strategy for targeted health promotion of sepsis.…”
Section: Implications For Clinicians Researchers and Policy Makersmentioning
confidence: 99%
“…If this is the case, strategies to increase awareness and improve health seeking behaviour in men may lead to more timely recognition and treatment of infection, thus reducing the risk of onset of organ failure, and therefore sepsis. A recent observational study of health promotional material in facility waiting rooms in NSW indicated only 3.1% of health promotional materials were male specific, compared to 15.3% female specific health promotion materials, 25 presenting one potential strategy for targeted health promotion of sepsis.…”
Section: Implications For Clinicians Researchers and Policy Makersmentioning
confidence: 99%
“…A study of printed health promotion materials (including posters, brochures and booklets) in GP and other health facility waiting rooms in Australia found that female‐specific literature outnumbered male‐specific literature by a ratio of 5:1 12 . This could contribute to a perception by some men that health services have not been designed with them in mind.…”
Section: Barriers To Accessmentioning
confidence: 99%